(untitled) (Research, Society and Development, 2023)
Medicinal plants with antimicrobial potencial marketed by rooters in a public market in the city of Maceió - AL. The habit of using medicinal plants is obtaining place or space, and every day natural medicines are being valued more in the current market. This study objective was to know lots of plants indicated by the raizeiros with antimicrobial action. Research by census of descriptive nature, with quantitative approach, that was done through the ethnobotanical and pharmacological knowledge of traders of medicinal plants in the flea market. The research was clarified to the raizeiros and those who agreed to participate signed the Informed Consent Form (ICF), as well as answering a pre-established questionnaire containing questions about the knowledge of the use of medicinal plants with antimicrobial activity to fight against infections. Raizeiros that were between twenty and sixty years old, being traders of plants with 5 months to 35 years in the labor market. Fifty medicinal plants were cited, but 27 species in 21 botanical families were important for the study cited by the raizeiros; 5 vegetables were highlighted: aroeira, barbatimão, mastruz, sambacaita and yellow uchi. With the advancement of information and communication technology, many people are still looking for natural ways to treat and their possible cure of illnesses.